Herbicide Residues in Water Resources: A Scoping Review - Sahand Jorfi; Fakher Rahim; Alireza Rahmani; Nematollah Jaafarzadeh; Zeinab Ghaedrahmat; Halime Almasi; Amir Zahedi (Hamadan University of Medical Sciences, 2021)
Several recent studies have focused on leaching pesticides from agricultural soils into surface and groundwater resources during irrigation. As a result, information about herbicide residues in water was necessary for conserving related resources. This study provided an overview of monitoring herbicides in water resources worldwide. In this scoping review, five databases were searched for publications (1990 to April 2021), including Scopus, PubMed/Medline, Cochrane library, Embase, and Web of Science. Among the 394 identified articles, 17 papers were selected for inclusion. Most of these studies have been conducted in regions with low herbicide concentrations, including Spain, Greece, Canada, Brazil, Hungary, Malawi, Portugal, Lesotho, Germany, Serbia, and the USA. The high-level alachlor, metolachlor, atrazine, metribuzin, and simazine herbicides in groundwater were detected in Portugal (0.4-13μg/L). An overview of studies demonstrated that herbicides are widely used in water resources, and surface waters are more contaminated than groundwaters.